In vivo evaluation of 4% articaine and 2% lignocaine intraligamentary injection administered with single tooth anesthesia-wand - Madhan Chenchugopal; Jayanthi Mungara; Nilaya Reddy Venumbaka; Arun Elangovan; Poornima Vijayakumar; Sakthivel Rajendran (Wolters Kluwer Medknow Publications, 2017)
Background: The available literature confirms the effectiveness of intraligamentary injections equal to nerve blocks and articaine equal to lignocaine with better depth of penetration for single tooth pulpectomy procedures with less postoperative soft tissue trauma. An advancement in the field of local anesthesia delivery is the Single Tooth Anesthesia-Wand (STA-Wand) which is relatively pain-free and offers comfort to the child. Aims: This study aims to evaluate and compare the anesthetic effectiveness and postoperative complications of 4% articaine and 2% lignocaine intraligamentary injection administered as single tooth anesthesia using a computer-controlled local anesthetic delivery system, the STA-Wand. Settings and Design: Using a randomized, split-mouth, cross-over study design, twenty children aged 4-10 years who required bilateral mandibular pulpectomies were administered intraligamentary injections with 4% articaine and 2% lidocaine in two appointments using STA-Wand. Pain, anxiety, and cooperation levels were scored by an operator and an observer at four phases of treatment using Wong-Baker Faces Pain Rating Scale and Two-6 point Co-operation Anxiety Rating Scale. Results were tabulated and analyzed. Statistical Analysis: Mann-Whitney U-test, paired t-test, and Student's t-test. Results: Both the local anesthetic agents were equally effective with no significant difference (P > 0.05) throughout rest of the treatment procedure compared to injection phase in minimizing pain, anxiety, and gaining the cooperation levels of children whereas during injection phase, 4% articaine showed superior effectiveness in minimizing pain compared to 2% lignocaine (P = 0.054). Conclusion: Both the local anesthetic agents delivered using STA-Wand is clinically acceptable, effective, and safe for usage in children.